Implementation of a lean manufacturing culture in the power generation equipment sector: a comparative analysis between theory and practice - Molinero, Guilherme Escarabelin; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2022)
Lean Manufacturing is one of the main applied philosophies to increase productivity due to Toyota’s great success and further expansion to the automotive industry. This continuous improvement culture has been studied by several authors and decomposed into steps and methodologies to implement and control, however several studies point to an elevated failure rate on lean replication. In this context, the objective was to study the implementation of a lean manufacturing culture into renewable energy component’s manufacturing. The study method was applied through a case study with data collection based on semi-structured interviews in a group of specialists from a company in the renewable energy sector, also being comparative to the lean manufacturing literature. Based on results, was understood tree main processes that constitutes the lean manufacturing implementation in this sector: Hoshin Kanri, Value Stream Mapping and Kaizen events. Results were compared with the literature to identify differences and based on the comparison, improvement suggestions were developed for the implementation of these tree processes in the studied company.
Keywords: Lean; Energy; Production